The Feminine Face of Romanticism in the Light of the 19th Century Dictionaries of the Russian Women Writers - Dąbrowska, Magdalena (Poznańskie Studia Slawistyczne, 2023)
The paper presents four dictionaries of the Russian women writers from the perspective of the history of Romanticism in Russia and the presence of women in it. There are: 1. The Bibliographical Catalogue of the Russian Women Writers (1826) by S.Russov, 2. The Materials to the History of the Russian Women Writers (1830, 1833) by M. Makarov, 3. The Bibliographical Dictionary of the Russian Women Writers (1889) by N. Golitsyn, 4. Our Women Writers (1891) by S. Ponomaryov. The paper consists of four parts: 1. The opening remarks (the history of the dictionaries of the Russian women writers in 19th and 21st centuries), 2. The publicists in Romanticism about the women (the article About the Women, “Damsky Zhurnal”, Moscow 1832, the alleged author P. Shalikov; the article About the Russian Women Writers by I. Kireyevsky (the almanac “Podarok Bednym”, Odesa 1834), 3. The representatives of Romanticism in the dictionaries, 4. The ending.